A phylogenetic analysis of Sciomyzidae (Diptera) and some related genera. (2nd November 2012) - Tóthová, Andrea; Rozkošný, Rudolf; Knutson, Lloyd; Kutty, Sujatha Narayanan; Wiegmann, Brian M.; Meier, Rudolf
Abstract: Sciomyzidae is a family of acalyptrate flies with 546 species in 61 genera that is among the most extensively studied groups of higher Diptera. Most of the known larvae are obligate enemies of Gastropoda. Hundreds of studies published over the past 50 years have resulted in detailed information concerning morphology of adults and immature stages, biology, development, behaviour, phenology and distribution. However, studies of phylogenetic relationships are based almost exclusively on morphological characters of adults, and no comprehensive molecular analysis across the family has been published. Here we fill this void by generating and analysing molecular data for 54 species of Sciomyzidae (22 genera), including Phaeomyiidae (one genus), and seven representative species of five other families of Sciomyzoidea (Coelopidae, Dryomyzidae, Helcomyzidae, Heteromyzidae and Huttoninidae) as outgroups. The reconstruction is based on morphological characters as well as nucleotide sequences for genes from the mitochondrial (12S, 16S, COI, COII, Cytb) and nuclear genome (28S, EF1α). The results are compared with recent morphological analyses. Our analyses support the monophyly of Sciomyzidae + Phaeomyiidae, and place Phaeomyiinae as a unique lineage within Sciomyzidae. A modified classification comprising three subfamilies is proposed. The major subfamily, Sciomyzinae, consists of two monophyletic and well separated groups, the tribes Sciomyzini and Tetanocerini.